Conservation Agriculture: A greener, smarter and economic way to grow food - Thierfelder, Christian L.; Nkosi, Phindiwe (CGIAR System Organization, 2023)
This is a blog about how Conservation Agriculture can be a game changer in alleviating factors such as poverty, climate change, increasing conflicts, lack of economic means and various underlying environmental factors which can and do impact agricultural productivity negatively.